Project Based Learning Workshop for Panggang Island & Pramuka Island, Seribu Island PAUD Educators - Dhieni, Nurbiana; Wulan, Sri; Gunarti, Winda; Sartika, Dewi; Azka, Haula Millati (CV Media Inti Teknologi, 2024)
This activity aims to increase the knowledge of 80% of teachers about the practice of Project Based Learning in early childhood education learning. The Project Based Learning workshop activities were held on Panggang and Pramuka islands, the Thousand Islands, and were attended by 14 teachers. The method uses lectures and workshop activities. The pre-test and post-test results showed that the average knowledge increased from 26.43 to 54.29. Based on the results of the Wilcoxon test analysis, a p-value of 0.002 < 0.05 was obtained, which means that the level of knowledge of the respondents changed before and after the Project Based Learning workshop was conducted. So, it can be concluded that the implementation of the project based learning workshop has been carried out well, from planning to implementation. Apart from that, teachers are also enthusiastic about the activities that have been carried out and are able to participate in the activities well.